(untitled) (Universal International Scientific Journal, 2026)
This study examines teaching ‘Jack’ proverbs to Uzbek learners: multifaceted challenges and effective teaching strategies. Content analysis of The Oxford Dictionary of Proverbs and selected course books revealed difficulties in polysemy, figurative meaning, pragmatic interpretation, stylistic features, and cross-linguistic interference. To address these, the study proposes various learner-centered strategies. A task-based learning sample illustrates practical classroom application, promoting contextualized, learner-centered instruction. The study focuses on Jack proverbs due to their frequency and relevance in course books, the tasks can be adapted to learners’ proficiency and interests. Further research may apply these instructional strategies to proverbs containing different anthroponyms to foster deeper figurative and cultural understanding